Efficacy and Safety of Acupuncture on Symptomatic Improvement in Primary Sjögren’s Syndrome: A Randomized Controlled Trial - Zhou, Xinyao; Xu, Haodong; Chen, Jinzhou; Wu, Hengbo; Zhang, Yi; Tian, Feng; Tang, Xiaopo; Zhang, Huadong; Ge, Lin; Li, Kesong; Jiang, Wen; Liu, Zhishun; et al. (Frontiers in Medicine, 2022)
Aim We sought to evaluate the efficacy of acupuncture in treating the main symptoms of primary Sjögren’s syndrome, specifically dryness, pain, and fatigue. Methods A total of 120 patients with primary Sjögren’s syndrome were randomized in a parallel-group, controlled trial. Participants received acupuncture or sham acupuncture for the first 8 weeks, then were followed for 16 weeks thereafter. The primary outcome was the proportion of participants with a ≥ 30% reduction in ≥ 2 of 3 numeric analog scale scores for dryness, pain, and fatigue. The secondary outcomes included the European League Against Rheumatism (EULAR) Sjögren’s Syndrome Patient-reported Index (ESSPRI); the EULAR Sjögren’s Syndrome Disease Activity Index; the Schirmer test score; unstimulated saliva flow; serum immunoglobulin G, A, and M concentrations; the Medical Outcome Study Short Form 36 score; salivary gland ultrasound imaging; and the Hospital Anxiety and Depression Scale score. Results The proportions of patients meeting the primary endpoint were 28.33% (17/60) in the acupuncture group and 31.66% (19/60) in the sham group, without a statistically significant difference (P = 0.705). The IgG concentration at week 16 and the homogeneity in ultrasonography of the salivary glands at week 8 showed significant differences between the 2 groups (P = 0.0490 and P = 0.0334, respectively). No other differences were observed between the 2 groups. ESSPRI and unstimulated saliva flow were improved in both groups compared to baseline, albeit with a significant difference between them. Conclusion In patients with primary Sjögren’s syndrome, acupuncture did not satisfactorily improve symptoms compared to placebo. However, interesting discoveries and possible underlying reasons were demonstrated and discussed, which may be useful to studies in the future. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT02691377].